Patchouli oil extraction by using hydro distillation (lab scale) - Muhamad khuzaifah, Mustakim (2008)
Patchouli or its scientific name Pogostemon cablin, is used in variety of field. For example it is used in Pharmaceutical industry as effective for fungal or bacterial infection and is of great help for insect bite. Patchouli essential oil is mostly used in perfumery industry as product of cosmetic and fragrance oil. The objectives of this research are to study the effect of extraction time and particle size of the leave on the yield of patchouli essential oil. Effects of extraction time and particle size (grinded and non grinded leave) were studied on the yield of patchouli essential oil. The extraction process is performed by using hydro distillation method. Extraction time is varied at 1, 2, 3 and 4 hours and the extraction process is repeated several times on grinded and non grinded patchouli leave. The essential oil obtained, was analyzed by using GC-MS. From the result, the yield of patchouli essential oil is increased as extraction time increased for both grinded and non grinded leave. The highest yield of grinded and non grinded patchouli leave is at four hours in which 1.32% and 0.89% of yield was obtained respectively. From the result also, grinded patchouli leave produces more oil than non grinded patchouli leave.